Refinement Behavior of Scrap Silicon by Mechanical Milling - Md. Raihanuzzaman, Rumman; Song, Joon-Woo; Lee, Ilseuk; Hong, Soon-Jik; Myung Koo, Jar (Current Nanoscience, 2014)
In this research, the refinement behavior of scrap silicon during mechanical milling with varying time was observed. Initial premilled Si powder with 106µm size was milled using high energy ball milling equipment in order to produce commercially applicable 10 µm target Si powders. Milling time was changed from 1 min to 60min while the characteristics and morphological changes of the powders according to the milling time were observed by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and X-ray diffractometer (XRD). The average particle size was found to have reached 10μm after a short milling time of 20 30 min, while 60min of milling yielded fine spherical particles of around 3.5 µm, surrounded by fine nanoparticles. In addition, it has also been found that there is presence of nano Si particles after 60 minutes of milling. The refinement mechanism suggests that the longer the milling time, the finer the powder size becomes with identifiable stages observed in between.
Keywords: High-energy milling